Pandangan Ibubapa yang Menghantar Anak-Anak ke Sekolah Agama Rakyat di Negeri Kedah dan Kelantan Terhadap Sains dan Teknologi - Mohd Radhi Ibrahim; Abdul Rahim Arsyad (Universiti Sains Islam Malaysia, 2024)
This research is an attempt to investigate the perception of the parents who sending their children at Sekolah Agama Rakyat (SAR) in Kedah and Kelantan regarding Science and Technology. The aim of research is to explore the rate of understanding of parents who send their children to SAR pertaining science and technology. The Methodology used in this research is a combination of library and field research with the questioner become most widely used instrument from 100 respondents. The research analysis found out that there are still many parents who are not aware of the importance of science and technology and it's relation with Islam.